PENGARUH KEMAMPUAN AWAL DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS VII DI MTS SARJI AR- RASYID SITUBONDO - Ritna Lindawati; Irma Noervadila; Zainul Munawwir (STKIP PGRI SITUBONDO, 2021)
Every student wants good learning outcomes. Factors that can influence students are initial ability and learning motivation. This research is non-experimental quantitative research. The type of research used is ex-post facto. In this study, there are three variables to be examined. Two independent variables include initial ability (X1) and motivation to learn (X2). While the dependent variable is the learning outcome (Y). The collected data were analyzed by the SPSS 18.0 software application. Furthermore, the Pearson product-moment partial correlation test, multiple linear regression test and multiple correlation tests were carried out. The multiple linear regression equation obtained is y = 9.965 + 0.819 X1 + 0.153 X2. If the initial ability variables (X1) and learning motivation (X2) are constant, the learning outcomes (Y) have increased by 9.965%. If the initial ability (X1) increases by 1% with the assumption that learning motivation (X2) is constant, then learning outcomes (Y) have increased by 8.19%. If the learning motivation (X2) increases by 1% assuming the initial ability (X1) is constant, then there is an increase of 1.53%.